In-vitro Evaluation of Different Botanicals Against Alternaria alternata Causing Alternaria Leaf Spot of Ber (Zizyphus mauritiana Lamk.) - Chaudhary, Shivani; Singh, H. K. (International Journal of Economic Plants, 2021)
Evaluation of different botanicals against alternaria leaf spot of ber (Zizyphus mauritiana Lamk.) was done under in-vitro at the NDUAT, Kumarganj main experiment station of Horticulture and Plant Pathology laboratory during 2018 to 2020. The fungus was isolated from the infected leaves of ber plant and cultural and morphological study was done through Poison Food Technique to confirm that the fungus was Alternaria alternata having branched and septate mycelium with light brown to blackish conidiophores in acropetal chain and the conidia having olive green to dark brown colour with transverse and longitudinal septa. The growth of the fungus was tested with botanicals. The nine different botanicals ie. Azadirachta indica (Neem), Allium sativum (Garlic), Parthenium hysterophorus (Parthenium), Ocimum sanctum (Tulsi), Datura stramonium (Dhatura), Curcuma longa (Turmeric), Zingiber officinale (Ginger), Allium cepa (Onion), Eucalyptus oblique (Eucalyptus) were tested against A. alternata infection in ber leaves. 100-gram leaves or cloves or rhizomes from each plant were collected and after washing extract was prepared in 100 ml distilled water. The extract was filtered through muslin cloth and then sterilized by passing them through a Millipore filter using a swimming filter adapter. All the botanicals were tested at 10%, 15% and 20% concentration, out of which garlic (74.88%) showed maximum mycelium growth inhibition followed by ginger (73.51%) and neem (69.25%), while minimum inhibition was found by Parthenium (34.64%) followed by Dhatura (53.37). It was concluded that the botanicals are also effective in controlling the alternaria leaf spot of ber.